Ultra-processed foods and the nutritional dietary profile in Brazil - Maria Laura da Costa Louzada; Ana Paula Bortoletto Martins; Daniela Silva Canella; Larissa Galastri Baraldi; Renata Bertazzi Levy; Rafael Moreira Claro; Jean-Claude Moubarac; Geoffrey Cannon; Carlos Augusto Monteiro (Universidade de São Paulo, 2015)
OBJECTIVE To assess the impact of consuming ultra-processed foods on the nutritional dietary profile in Brazil. METHODS Cross-sectional study conducted with data from the module on individual food consumption from the 2008-2009 Pesquisa de Orçamentos Familiares (POF - Brazilian Family Budgets Survey). The sample, which represented the section of the Brazilian population aged 10 years or over, involved 32,898 individuals. Food consumption was evaluated by two 24-hour food records. The consumed food items were classified into three groups: natural or minimally processed, including culinary preparations with these foods used as a base; processed; and ultra-processed. RESULTS The average daily energy consumption per capita was 1,866 kcal, with 69.5% being provided by natural or minimally processed foods, 9.0% by processed foods and 21.5% by ultra-processed food. The nutritional profile of the fraction of ultra-processed food consumption showed higher energy density, higher overall fat content, higher saturated and trans fat, higher levels of free sugar and less fiber, protein, sodium and potassium, when compared to the fraction of consumption related to natural or minimally processed foods. Ultra-processed foods presented generally unfavorable characteristics when compared to processed foods. Greater inclusion of ultra-processed foods in the diet resulted in a general deterioration in the dietary nutritional profile. The indicators of the nutritional dietary profile of Brazilians who consumed less ultra-processed foods, with the exception of sodium, are the stratum of the population closer to international recommendations for a healthy diet. CONCLUSIONS The results from this study highlight the damage to health that is arising based on the observed trend in Brazil of replacing traditional meals, based on natural or minimally processed foods, with ultra-processed foods. These results also support the recommendation of avoiding the consumption of these kinds of foods.